Entanglement of CCR5 and Alzheimer’s Disease - Li, Tianwen; Zhu, Jianhong (Frontiers in Aging Neuroscience, 2019)
Although the mechanisms of Alzheimer's disease are diverse and unclear, the past 20 years have witnessed the unprecedented development of the AD inflammation theory. As a key inflammatory receptor family, the C-C chemokine receptor family is a remarkable participant in the cause of Alzheimer's disease; of this family, CCR5 is the most widely studied. CCR5 is an essential entrance when HIV infects immune cells and is also involved in other inflammatory and immune activities. New evidence on the inevitably intertwined link between Alzheimer's disease and CCR5 indicates that CCR5 accelerates the development of Alzheimer's disease, and few studies disputed it. The role of CCR5 in Alzheimer's disease remains elusive. However, as the research progresses, this intricate relationship will gradually be uncovered.